2022
DOI: 10.1021/acsami.2c11286
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Tumor Immunotherapy through a Single Injection of Injectable Antigen/Adjuvant-Loaded Macroporous Silk Fibroin Microspheres

Abstract: Synthetic or natural materials have been used as vaccines in cancer immunotherapy. However, using them as vaccines necessitates multiple injections or surgical implantations. To tackle such daunting challenges, we develop an injectable macroporous Bombyx mori (B. mori) silk fibroin (SF) microsphere loaded with antigens and immune adjuvants to suppress established tumors with only a single injection. SF microspheres can serve as a scaffold by injection and avoid surgical injury as seen in traditional scaffold v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…This effectively inhibited tumor growth by increasing cytotoxic T lymphocyte response (Fig. 14 A, B) [ 115 ]. SF-based tumor immunotherapy has broad application prospects, but the compatibility and safety of SF-loaded NPs have not been comprehensively discussed [ 202 , 204 ].…”
Section: Biomaterials Used In Tumor Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…This effectively inhibited tumor growth by increasing cytotoxic T lymphocyte response (Fig. 14 A, B) [ 115 ]. SF-based tumor immunotherapy has broad application prospects, but the compatibility and safety of SF-loaded NPs have not been comprehensively discussed [ 202 , 204 ].…”
Section: Biomaterials Used In Tumor Immunotherapymentioning
confidence: 99%
“…(d) H&E staining and TUNEL staining of B16F10-OVA tumors in the mice at day 18. (Reproduced with permission from [ 115 ] Copyright © 2022, American Chemical Society)
Fig. 15 Surgery-free injectable CAR-T cells delivery system for tumor immunotherapy.
…”
Section: Biomaterials Used In Tumor Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…This means processing SF into microspheres might be a solution to develop efficient SF sunscreens. At the same time, our previous studies have developed various technologies to control the size of SF spheres from nano to micro for potential applications of tissue engineering and drug delivery. Therefore, it is feasible to prepare SF into microspheres to avoid the diffraction of the UV light for enhancing the function of UV-protection.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has found that silk fibroin (SF) can be developed into a drug delivery system. SF is a natural protein derived from silkworm cocoons and has several advantages over other carriers, such as synthetic polymers , and liposomes. , It is biocompatible, biodegradable, and can be processed into biomaterials of various sizes and shapes . Furthermore, the resultant biomaterials are expected to protect the loaded cargo from degradation and enhance its stability .…”
Section: Introductionmentioning
confidence: 99%